Risk‐Taking by Young People in Late Adolescence Increases When They Perceive the Possibility of Their Peer "Observing Someday". (3rd February 2020) - Moriizumi, Shingo; Usui, Shinnosuke
Abstract: This experimental study on risk‐taking by young people in their late adolescence was carried out from the perspective of peer effect. A gambling task was administered to 42 young people under the following experiment conditions: with or without the possibility that the experiment results would be disclosed at some time to their peers and information about their peers being more or less risk‐oriented. The results showed that when it was suggested that the experiment results would be disclosed in some time and when the peer was perceived as more risk‐oriented, there was a peer effect. However, when the peer was perceived as less risk‐oriented, no peer effect occurred. The findings of this study confirmed that, while there is some room for further testing, when it was suggested that the experiment result might be disclosed to the peer, even under a condition in which only a single participant was involved, there was a peer effect, unlike in previous studies.